Financial performance analysis at PT. Japfa Comfeed Indonesia Tbk, 2017-2019 : - Surono Surono; Mohamad Djadjuli; Itat Tatmimah; Fitriya Sari; Muzayyanah Muzayyanah (Institute of Computer Science (IOCS), 2023)
Financial performance is a description of the company's financial condition in a certain period, both regarding the aspects of raising funds and channeling funds which are usually measured by indicators of capital adequacy. Therefore, to be able to measure financial performance in companies usually use financial ratio. Financial ratios commonly used in companies such as liquidity ratio, solvency ratio, profitability ratio, activity ratio and investment ratio. However, this study only uses three financial ratio, namely liquidity ratio, solvency ratio and profitability ratio. Based on the research results, the results of the analysis of the liquidity ratio, solvency ratio and profitability ratio in the company have fluctuated or are still unstable in each period because they have increased and decreased in each period.